How to Manage Stunting Patients through Policy: Using Community Empowerment - Sudirman, Sudirman; Rupita, Rupita; Herlan, Herlan; Yulianti, Yulianti; Alamri, Annisa Rizqa (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
Empowerment of Human Resources, Enterprises, Environment, and Institutions (Penelitian Pada Istri Nelayan Tradisional Desa Pulau Limbung Kecamatan Sungai-Raya Kabupaten Kubu Raya). Research techniques and tools include in-depth interviews, non-participation observations, focus group discussions (FGD), document studies as well as documentation, data reduction analysis, presentation of analyzed data, and drawing conclusions. Treatment of stunting sufferers involves: (1) empowerment of SDM; objectives; improving knowledge and understanding of mothers about the health  and nutritional needs of their children aged 1–5 years (Balita). Formation of activities of counseling and guidance fulfilling the nutritional requirements of Balita; (2) Empowering traditional fishermen's enterprises; aims; (a) increase the income of fisherman; and (b) fulfillment of the living needs of family members. Form activities; develop vegetable crop cultivation and live pharmacies; (3) enrich the living environment and its purpose; improve citizens' knowledge of hygiene and the health of the environment; and encourage citizens to create clean, healthy, and comfortable settlements. Forms of activities: sanitation, hygiene movement, and tree planting movement; (4) institutional promotion, whose goal is to enhance the role of institutional development of prasarana and health facilities, treatment of health problems and stunting sufferers, and development of the enterprises of villagers. Obstacles to the management of stunting sufferings: (a) poor knowledge and awareness of mothers about health; (b) the day-to-day busy work for mothers in palm coconut farms; (c) limited health facilities and facilities; and (d) the geographical conditions of the island village are still difficult to reach.gb777